MEDIA GAMBAR DALAM KEGIATAN PEMBELAJARAN BERHITUNG SISWA PEMULA PENDIDKAN DASAR - Eliyah Eliyah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
This study aims to explore information about the use of image media from the point of view of its strengths, weaknesses and uses in the design of learning activities. The results of this study are a solution to the concept of image media weaknesses and refer to the advantages of image media: (1) The use of image media should pay attention to the results of research that show the most appropriate methods of using images and attract the most attention of students. (2) The pictures used are pictures that are very relevant to the material being taught. (3) Drawings should be close to realistic. (4) Avoiding images that will create negative impressions. (5) The pictures used should be adjusted to the student's academic and psychological development. (6) Teachers 'delivery techniques and methods should be able to attract students' interest and attention. What does it mean that media is good but not supported by competent teacher capabilities. (7) The results showed that the motion cues shown by the pictures resulted in better understanding for students. In the sense of combining visual media, audio in audio-visual form or if possible more than that it is better if possible a teacher can do it.